Development of Learning Videos Based on Problem-Solving Characteristics of Animals and Their Habitats Contain in Ipa Subjects on 6th-Grade - Andriyani, Ni Luh; Suniasih, Ni Wayan (Universitas Pendidikan Ganesha, 2021)
Lack of available learning media in the form of videos in a bold learning process during the Covid-19 pandemic, so that it has not been able to attract students' attention while studying. This study aimed to develop a learning media video based on problem-solving in IPA subjects, and its feasibility has been tested according to expert test evaluations and individual trials. The type of this research is a development using the ADDIE model. The method used to collect data was a questionnaire equipped with interviews and observations. The data analysis used was descriptive quantitative and qualitative analysis. The subject of this research was the development of learning video media. The assessment results from the product trial stage by subject content experts were 100%, that was categorized great, by the instructional design experts was 91.67%, that was categorized great, by the expert of learning media was 93.3%, that was categorized great, and individual testing obtained 95, 23%, which were also categorized great. Implicated learning videos are by improving the thinking way of students to think higher is not only in the IPA subject but also in the other subjects. Thus, it can be concluded that the learning video product based on problem-solving is feasible to be used in the learning process.